Predictors of nomophobia and online identity : the contribution of nostalgia to phone and online attachment - d´Orey, Maria Francisca Paulino da Câmara (2020)
The presence of smartphones in everyday life has become so frequent that people cannot spend a day without checking their phones. This recent addition is defined as nomophobia, the dependency on mobile phones and the need to be constantly online, as a way to ensure one’s online presence, i.e. self-sense of online identity. However, what predicts such a need? Based on theoretical reasoning, I suggest that nostalgia, or the self-selection of positive content from the past, is associated with this dependency. Although brands began to develop content that evokes old memories, i.e. nostalgia, to link consumers with positive content from the past, it is still missing to understand the relation between nostalgia and nomophobia/online identity. In this sense, the present dissertation investigated if nostalgia predicts nomophobia/online identity and, subsequently, if this relationship is moderated by age and gender. To this end, six hypotheses, testing the relationship between nostalgia and nomophobia/online identity and their potential moderators, were elaborated. Results showed that higher levels of nostalgia translated into higher levels of nomophobia and online identity. This may be explained by the sense of continuity that nostalgia promotes. However, this relationship is not moderated by age or gender. This means that a sense of self-continuity might be a similar need across individuals. Learning this, digital marketers and brands with online presence will be able to improve their campaigns with nostalgic content, contributing to extend consumers’ online identity.